COVID-19 vaccine uptake, hesitancy and clinical effects on patients with Takayasu’s arteritis: A web-based questionnaire survey from a large cohort - Kong, Xiufang; Dai, Xiaojuan; Ma, Lingying; Wang, Jinghua; Sun, Ying; Jiang, Lindi (Frontiers in Immunology, 2023)
Objective: This study aimed to investigate the Coronavirus disease 2019 (COVID-19) vaccination rate, reasons for vaccine hesitancy and clinical effects on patients with Takayasu's arteritis (TAK). Methods: A web-based survey was administered to a TAK cohort established by the Department of Rheumatology, Zhongshan Hospital through WeChat in April, 2022. Responses from a total of 302 patients were received. The Sinovac or Sinopharm inactivated vaccination rate, side effects, and vaccine hesitancy reasons were analyzed. In addition, disease flare, new disease onset, and changes of immune-related parameters after vaccination were analyzed in vaccinated patients. Results: Among 302 patients, 93 (30.79%) received the inactivated COVID-19 vaccination. Among the 209 unvaccinated patients, the most common reason for hesitancy were concern about side effects (136, 65.07%). Vaccinated patients had a longer disease duration (p = 0.08) and lower use of biologic agents (p < 0.001); 16 (17.20%) of the 93 vaccinated patients developed side effects, and most of them were mild; 8 (8.60%) developed disease flares or new-onset disease 12-128 days post-vaccination and 2 (2.15%) developed serious adverse effects (vision defect and cranial infarction). Immune-related parameters of 17 patients indicated decreases in IgA and IgM after vaccination (p < 0.05). Eighteen (19.35%) of the 93 vaccinated patients were diagnosed post-vaccination.These patients had a significantly higher percentage of CD19+ B cells at disease onset (p < 0.05) than the unvaccinated patients diagnosed at the same time. Conclusion: The vaccination rate was low in TAK, which was mainly caused by concerns about negative effects of vaccination on their disease. An acceptable safety profile was observed in vaccinated patients. The risk of disease flare associated with COVID-19 vaccination warrants further investigation.